2007
DOI: 10.1002/ange.200700298
|View full text |Cite
|
Sign up to set email alerts
|

Systematically Probing the Effect of Catalyst Acidity in a Hydrogen‐Bond‐Catalyzed Enantioselective Reaction

Abstract: Hydrogen bonding is ubiquitous in nature and is a prevalent mode of substrate activation in enzymes. Recently, chemists have begun to exploit this mode of activation in asymmetric catalysis by designing synthetic catalysts that use hydrogen bonds. [1][2][3] These catalysts feature a variety of structural motifs and hydrogen-bond-donating functional groups. In light of the rapid development of new hydrogen-bond-catalyzed reactions, we felt that a greater understanding of the connection between catalyst activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 29 publications
1
15
0
1
Order By: Relevance
“…For both reactions, it was found that single-point activation of the dienophile resulted in a more efficient lowering of the reaction barrier, thereby confirming Rawal's hypothesis. This feature was exploited to carry out an experimental mechanistic study on the impact that catalyst acidity has on rate and selectivity in the previously described hDA reaction (Scheme 6.2) [19]. This result slightly revised the models for enantioselection originally proposed by Rawal et al [12] and, subsequently, by other authors based on computational studies at lower levels of theory, all of them featuring a π/π interaction between the phenyl ring of benzaldehyde and one naphthyl ring of TADDOL [16,17].…”
Section: Single-point Versus Two-point Activationmentioning
confidence: 99%
“…For both reactions, it was found that single-point activation of the dienophile resulted in a more efficient lowering of the reaction barrier, thereby confirming Rawal's hypothesis. This feature was exploited to carry out an experimental mechanistic study on the impact that catalyst acidity has on rate and selectivity in the previously described hDA reaction (Scheme 6.2) [19]. This result slightly revised the models for enantioselection originally proposed by Rawal et al [12] and, subsequently, by other authors based on computational studies at lower levels of theory, all of them featuring a π/π interaction between the phenyl ring of benzaldehyde and one naphthyl ring of TADDOL [16,17].…”
Section: Single-point Versus Two-point Activationmentioning
confidence: 99%
“…12 Another recent example in the field of homogeneous catalysis is a systematic study of catalyst activity as a function of the hydrogen bond donating ability of a catalyst (p K a ). 13 Finally, attempts to utilize QSAR methods to study catalysts for polymerization, 14 homogeneous, 15 and heterogeneous catalysis are on record. 16 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group has focused on the development of novel and easily accessible bifunctional N-acyl aminophosphine catalysts from amino acids, which has unambiguously proved valuable in all sorts of asymmetric cycloaddition reactions with allenoates. Subsequently, an examination of catalysts 4f-4l with different groups on the nitrogen was carried out (Table 1, entries [6][7][8][9][10][11][12]. Initially, 3-phenyloxindole 1a was chosen as pronucleophile in the g-addition with ethyl buta-2,3-dienoate 2 for evaluation by the catalysts 4a-4l (Table 1).…”
mentioning
confidence: 99%
“…Initially, 3-phenyloxindole 1a was chosen as pronucleophile in the g-addition with ethyl buta-2,3-dienoate 2 for evaluation by the catalysts 4a-4l (Table 1). [10] Introduction of a trifluoromethyl group into the catalyst 4f, which means a strong acidity on the NH functionality, turned out to be detrimental to the enantioselectivity, although an excellent yield was obtained (Table 1, entry 6). It was shown that the chiral backbones of these catalysts have a great effect on the enantioselectivity.…”
mentioning
confidence: 99%